Synthesis of 1, 4, 2‐Oxathiazoles via Norrish Type II Generation of Thiocarbonyls. Issue 35 (19th September 2019) - Ong, Michelle J. H.; Hewitt, Russell J.
Abstract: Several previously inaccessible 1, 4, 2‐oxathiazoles have been prepared by [3 + 2] cycloaddition of nitrile oxides and highly reactive thioaldehydes and thioketones. Generated via photolytic cleavage of 2‐phenacyl sulfides (Norrish type II photolytic cleavage), these reactive thiocarbonyls provide a broad library of 1, 4, 2‐oxathiazole structures which other methods have failed to achieve. We also report the thermal fragmentation of these 1, 4, 2‐oxathiazoles, in which both fragmentation to nitrile or isothiocyanate may occur. 5H‐1, 4, 2‐Oxathiazoles have shown to fragment to nitrile even in the absence of base. At elevated temperatures, fragmentation to isothiocyanates occurred in preference to nitriles. Abstract : A Norrish type II photolytic cleavage of 2‐phenacyl sulfides was used for the generation and in situ reaction of thiocarbonyl compounds to provide access to hitherto unknown 1, 4, 2‐oxathiazoles. The oxathiazoles were subjected to thermal fragmentation in which a variety of pathways were observed, in addition to the expected cleavage to isothiocyanates and carbonyls.